Advances in Artificial Intelligence, Software and Systems Engineering Joint Proceedings of the AHFE 2018 International Conference on Human Factors in Artificial Intelligence and Social Computing, Software and Systems Engineering, The Human Side of Service Engineering and Human Factors in Energy, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Ahram, Tareq Z.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book focuses on emerging issues following the integration of artificial intelligence systems in our daily lives. It focuses on the cognitive, visual, social and analytical aspects of computing and intelligent technologies, highlighting ways to improve technology acceptance, effectiveness, and efficiency. Topics such as responsibility, integration and training are discussed throughout. The book also reports on the latest advances in systems engineering, with a focus on societal challenges and next-generation systems and applications for meeting them. It also discusses applications in smart grids and infrastructures, systems engineering education as well as defense and aerospace. The book is based on both the AHFE 2018 International Conference on Human Factors in Artificial Intelligence and Social Computing, Software and Systems Engineering, The Human Side of Service Engineering and Human Factors in Energy, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA.
Part I: Software and Systems Engineering Applications -- Development of a web based framework to objectively compare and evaluate software solutions -- A case study of user adherence and software project performance barriers from a sociotechnical viewpoint -- DevOps for containerized applications -- Modelling of polymorphic user interfaces at the appropriate level of abstraction -- Guided terrain synthesis through distance transforms.
Keywords: Computational intelligence; Artificial intelligence; Software engineering; Cognitive psychology; Computational Intelligence; Artificial Intelligence; Software Engineering; Cognitive Psychology